PBL methodology in business administration and industrial engineering and management programs: similarities and differences - Alves, Anabela Carvalho (2018)
PBL has been implemented in many programs in the universities as a need to change pedagogical and learning practices from teacher-centred to student-centred methodologies. Business Administration from Brazil, Instituto Federal de Educação, Ciência e Tecnologia Fluminense and Industrial Engineering and Management from Portugal, Department of Production and Systems, University of Minho are two of such programs. PBL implies an innovative curriculum design that could assume many forms and be differently implemented. The aim of this paper is to describe these two different approaches of PBL, namely, focusing the differences related to: the program where was implemented, the coordination and organization, the courses implied, the teamwork organization, the assessment methods (e.g. formative, summative, self and peer), the related situations concerning implementation and development of PBL as learning approach (e.g. difficulties) and the final products expected from the project among others. Benefits for the students and teachers are also discussed in each PBL implementation. The instruments of the research methodology used were the experience of the authors, the documental analysis and the results of the students and teachers perceptions questionnaires by the project ending among others. This will give the opportunity for the authors and others researchers benefit from the best of each approach.